POLITIK HUKUM PERTAMBANGAN INDONESIA DAN PENGARUHNYA PADA PENGELOLAAN LINGKUNGAN HIDUP DI ERA OTONOMI DAERAH - Martha Pigome (Masalah-Masalah Hukum, 2011)
Politics Mining Law in Indonesia has undergone significant changes with the enactment of Law Number 4 of 2009 as elaboration of Article 33 Paragraph (3) and (4) of the 1945 Constitution. State through the goverment authorized to regulate the management of mining, in the era of regional authonomy Local Goverment have the authority to regulate and supervise the management or control of any existing mining businesses in the area with more emphasis on enivonmental management and environmentally sustainable. Kata kunci: Politik Hukum, Pertambangan, Lingkungan Hidup